Solving multi-objective scheduling problems : An integrated systems approach - Geiger, Martin Josef (2006)
In the past, numerous approaches have been formulated either for approximating Pareto-optimal alternatives or supporting the decision making process with an interactive multi criteria decision aiding methodology. The article on the other hand presents an integrated system for the resolution of problems under multiple objectives, combining both aspects. A method base of metaheuristics is made available for the identification of optimal alternatives of machine scheduling problems, and the selection of a most preferred solution is supported in an interactive decision making procedure. As the system is aimed at end users, a graphical interface allows the easy adaptation of metaheuristic techniques. Contrary to existing software class libraries, the system therefore enables users with little or no knowledge in the mentioned areas to successfully solve scheduling problems and customize and test metaheuristics. After successfully competing in the finals in Ronneby (Sweden), the software has been awarded the European Academic Software Award 2002